Ordeño limpio - Dávila, T. O.; Ramírez R., E. (CATIE, Turrialba (Costa Rica). INPASA, Managua (Nicaragua), 2021)
fotografías. Es parte del Proyecto enfoques silvopastoriles integrados para el manejo de ecosistemas